Project communication aspects on construction performance: Investigating contractors’ perspective - Yu, Chooi Yi (2022)
The construction sector is plagued by ineffective communication management resulting in time and cost overruns. It has been discovered that over 70% of contractors' time is spent on communication with other stakeholders. Contracting parties as one of the major construction practitioners are underexplored to enhance project performance. Therefore, it is imperative to look at contractors' perspectives on project communication. This research ascertains the significance of effective communication, factors of communication that contribute to poor performance and practical strategies to improve communication effectiveness in construction projects. First, research questions and objectives were identified based on a comprehensive review of existing literature. A total of 120 valid responses were received from contracting parties through quantitative research methodology conducted in the Klang Valley region, with a response rate of 38.10%. The data collected were further evaluated through reliability analysis, descriptive statistics and inferential statistics. The three most critical needs of effective communication were revealed as "reduce conflict", "better collaboration between parties" and "good problem solving". Also, "lack of effective communication techniques", "frequent changes to contract", "lack of mutual respect and trust", "slow information flow", and "unethical behaviour" have been categorised as the top five negative factors of communication that impact project performance. As the top three recommended measures were revealed as "understand client's needs", "use effective communication channel", and "maintain integrity and trust". The research's findings also revealed the significant discrepancies in respondents' perceptions regarding the reasons and potential measures for communication effectiveness. A strong correlation was found by using Spearman's correlations test between the "lack of mutual respect and trust" and "ability to maintain integrity and trust". Five principal dimensions were identified, comprising (1) unique nature of construction industry; (2) supportive communication management; (3) communication's knowledge; (4) organisational gap and technological viewpoint; and (5) organisational culture. In short, this research's findings able to improve the construction industry's performance by allowing contracting parties to understand the importance of communication and address them with effective communication techniques.